2021
DOI: 10.1155/2021/8876906
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Comparison of Postoperative Pain and Complications after Thyroidectomy under Different Anesthetic Techniques: Volatile Anesthesia versus Total Intravenous Anesthesia

Abstract: While the postoperative outcome is favorable, post-thyroidectomy pain is considerable. Reducing the postoperative acute pain, therefore, is considered important. This study investigated whether the pain intensity and need for rescue analgesics during the immediate postoperative period after thyroidectomy differ according to the methods of anesthesia. Seventy-two patients undergoing total thyroidectomy under general anesthesia were examined. Patients were randomly assigned to undergo either total intravenous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
17

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 24 publications
0
6
1
17
Order By: Relevance
“…Similarly, morphine doses in the recovery room were significantly increased in this subset compared to the inhaled anesthesia group. 21 In comparison, our study did not find a significant difference in pain medications (narcotics, nonnarcotics, or either) or oral MME doses administered to either cohort in the PACU.…”
Section: Discussioncontrasting
confidence: 69%
“…Similarly, morphine doses in the recovery room were significantly increased in this subset compared to the inhaled anesthesia group. 21 In comparison, our study did not find a significant difference in pain medications (narcotics, nonnarcotics, or either) or oral MME doses administered to either cohort in the PACU.…”
Section: Discussioncontrasting
confidence: 69%
“…A postoperative pain numerical rating scale showed a significantly higher mean score for TIVA patients (5.7) versus inhalational patients (4.7). Further, their TIVA patients required higher morphine equivalent doses in the PACU (16.7 vs. 14.1 mg) 21 . In a double‐blind randomized study of middle ear surgery patients, Mukherjee et al assessed 100 individuals receiving either TIVA with propofol‐remifentanil or a balanced anesthesia approach with fentanyl, propofol, and isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…Further, their TIVA patients required higher morphine equivalent doses in the PACU (16.7 vs. 14.1 mg). 21 In a double-blind randomized study of middle ear surgery patients, Mukherjee et al assessed 100 individuals receiving either TIVA with propofol-remifentanil or a balanced anesthesia approach with fentanyl, propofol, and isoflurane. In the PACU, TIVA patients had elevated pain scores, and required significantly more morphine.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in thyroid surgery, propofol-based TIVA has been associated with higher intensity of postoperative pain as well as higher postoperative opioid consumption [29 ▪ ]. Furthermore, other clinical studies have found no beneficial analgesic effects of propofol-based TIVA in hysterectomy and colon surgery [29 ▪ ,30].…”
Section: Postoperative Painmentioning
confidence: 99%